2022
DOI: 10.1002/advs.202103222
|View full text |Cite
|
Sign up to set email alerts
|

Exosome Processing and Characterization Approaches for Research and Technology Development

Abstract: Exosomes are extracellular vesicles that share components of their parent cells and are attractive in biotechnology and biomedical research as potential disease biomarkers as well as therapeutic agents. Crucial to realizing this potential is the ability to manufacture high‐quality exosomes; however, unlike biologics such as proteins, exosomes lack standardized Good Manufacturing Practices for their processing and characterization. Furthermore, there is a lack of well‐characterized reference exosome materials t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
141
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(173 citation statements)
references
References 370 publications
(534 reference statements)
3
141
0
Order By: Relevance
“…This LOD is comparable to that reported by CE-LIF with the EVs stained by membrane-bound dyes . CE is not as sensitive as NTA and ELISA, , two common techniques used for EV quantification; however, ELISA is time-consuming and NTA can quantify only highly purified EVs. , CE also provides the benefit of low sample consumption and good reproducibility. Overall, our results well support the possibility of using CE to quantify the EVs eluted by AF4 in the following study.…”
Section: Resultssupporting
confidence: 60%
“…This LOD is comparable to that reported by CE-LIF with the EVs stained by membrane-bound dyes . CE is not as sensitive as NTA and ELISA, , two common techniques used for EV quantification; however, ELISA is time-consuming and NTA can quantify only highly purified EVs. , CE also provides the benefit of low sample consumption and good reproducibility. Overall, our results well support the possibility of using CE to quantify the EVs eluted by AF4 in the following study.…”
Section: Resultssupporting
confidence: 60%
“…MSCs derived sEVs are potential in biotechnology and biomedical research to develop as disease biomarkers as well as therapeutic agents [47]. The up-to-date studies also demonstrated that MSCs' sEVs is a promising therapeutic strategy for chronic pain.…”
Section: Discussionmentioning
confidence: 97%
“…The characterization methods for PDNVs follow established methods for mammalian EVs and are described in other reviews in detail [ 47 , 48 ]. Table 1 shows a concise list of frequently used methods for PDNVs.…”
Section: Isolation and Characterization Methods Of Pdnvsmentioning
confidence: 99%